Cognitive development of children with Kawasaki disease and the parenting stress of their caregivers in Taiwan: a case–control study. Issue 6 (3rd June 2021) - Wang, Liang-Jen; Tsai, Zi-Yu; Chang, Ling-Sai; Kuo, Ho-Chang
Abstract : Objective: Kawasaki disease (KD) is an acute form of febrile vasculitis that occurs in early childhood. The multisystemic vasculitis common in patients with KD may influence blood perfusion in the brain, and thus caregivers of children with KD may feel stress with regard to caring for them. Intravenous immunoglobulin (IVIG) infusion is the standard treatment for acute KD, and the most serious complication of KD is coronary artery aneurysms (coronary artery lesion (CAL)). This study aimed to investigate the relationships between KD heterogeneity and the risk of patients' cognitive impairment or caregivers' parenting stress. Design: A case–control study with consecutive sampling. Setting: A medical centre (Kaohsiung Chang Gung Memorial Hospital, Taiwan). Participants: This study consisted of 176 patients with KD (mean age: 5.5 years, 60.8% boys) and 85 healthy children (mean age: 6.4 years, 54.1% boys). Primary and secondary outcome measures: Based on the children's age, each patient with KD and control subject was administered an assessment using the Mullen Scales of Early Learning or the Wechsler Intelligence Scale, and parenting function of their caregivers was assessed using the Parenting Stress Index (PSI)-Short Form. Results: We observed no significant differences in any developmental index, cognitive function or parenting stress between patients with KD and controls. Among the children with KD, IVIG administration nor CAL was associated with children's cognitive scores. However, the caregivers of patients who had CAL suffered from greater PSI total scores than those of patients without CAL. Furthermore, the caregivers who had education levels of a master's degree or above showed less parenting stress than those who had an education level of college or lower. Conclusion: Caregivers' education is associated to parenting stress, and caregivers of patients with KD who developed CAL may feel stress about the unpredictable sequela caused by CAL for their children. Such caregivers may require support to fulfil their parenting roles.